The Impact of Electronic Customer Relationship Management (e-CRM) on e-Loyalty - Maudy Amalyah Dodhy Putri; Ananda Sabil Hussein; Radityo Putro Handrito (Jurnal Ilmiah Manajemen Kesatuan, 2025)
In the era of digital commerce, customer loyalty has become a vital determinant of platform sustainability. This study investigates the impact of Electronic Customer Relationship Management (e-CRM) on electronic loyalty (e-loyalty), with a focus on the mediating roles of e-customer experience and customer engagement. Grounded in Relationship Marketing Theory, the research targets active Tokopedia users in Indonesia using a quantitative approach. Data were collected through an online survey of 240 participants selected via purposive sampling, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that e-CRM significantly influences e-loyalty both directly and indirectly. Customer experience and engagement were found to mediate these relationships effectively. Notably, e-CRM improves digital experiences and promotes deeper customer involvement, both of which significantly enhance loyalty. These findings affirm that loyalty in e-commerce is driven not only by technical CRM execution but also by seamless, personalized interactions and emotional connections.